2016
DOI: 10.1097/pcc.0000000000000728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the “Early” Use of Albumin in Children with Extensive Burns: A Randomized Controlled Trial*

Abstract: Early albumin infusion in children with burns greater than 15-45% total body surface area reduced the need for crystalloid fluid infusion during resuscitation. Significantly fewer cases of fluid creep and shorter hospital stay were also observed in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 32 publications
0
19
0
4
Order By: Relevance
“…Of the 777 titles and abstracts reviewed, 108 full-text articles were retained for further screening. Seven studies met the inclusion criteria (figure 1; n=359) 22–28…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 777 titles and abstracts reviewed, 108 full-text articles were retained for further screening. Seven studies met the inclusion criteria (figure 1; n=359) 22–28…”
Section: Resultsmentioning
confidence: 99%
“…The seven studies that met the inclusion criteria were published between 1982 and 2016 (table 2). 22–28 Four studies were undertaken in the USA,22–24 28 with other studies carried out in Japan (n=1),27 Brazil (n=1)26 and China (n=1) 25. One randomised controlled trial,26 one cohort study,24 one prospective randomised study,23 two prospective observational studies25 28 and two retrospective observational studies22 27 were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reported less crystalloid volume, but it has low sample size (n = 23) so that a larger study were needed in the future. 30 Melinyshyn et al 8 use albumin 5% in burn resuscitation, but did not demonstrate difference in duration of mechanical ventilation, wound healing, length of stay, nor survival rate. Albumin supplementation also has been proven to be not beneficial in a randomized controlled trial by Greenhalgh et al, while it increases the cost.…”
Section: Discussionmentioning
confidence: 96%
“…Other reviews of the use of albumin in burns and trauma resuscitation have confirmed the lack of untoward effects, but evidence of benefit has been harder to come by. [13][14][15][16][17][18][19] In the basic science literature, our understanding of the microcirculation and the mechanisms responsible for oedema formation are radically changing, centreing on the role of the glycocalyx. [20] That colloid osmotic pressure does not play the role it was assigned by Ernest Starling is known to many burn surgeons, as burn oedema usually resolves in the face of dropping albumin levels.…”
Section: Den Hollander Respondsmentioning
confidence: 99%